Le procès de circulation du capital - Marx, Karl; Cogniot, Erna; Cohen-Solal, C.; Badia, Gilbert (Paris : Editions Sociales, 1953)
Bibliotheek François Vercammen
Frans
Meerdelige publicatie
Keywords: marxistische economie